Examining English Language Instructors’ Practice of Reflective Teaching Components in Ethiopia - Habtamu, Nigatu; Belay, Badima (Educational Challenges, 2023)
Reflective teaching, which has attracted attention globally as an integral component of teacher pedagogy, is still a difficult concept to understand. Probably, because it is attainable only when the practitioners are committed to practice it, seeing it as the best opportunity for their professional development through critical thinking about their teaching. The aim of this study is to examine the opportunities for English language instructors to engage in the practice of reflective teaching. Adopting convergent descriptive case study method, the study was conducted utilizing both qualitative and quantitative data sources. The quantitative data were collected through the administraton of a questionnaire. It was adopted from a Reflective English Language Teaching Inventory developed by Akbari et al for forty-one English language instructors taken through comprehensive sampling in Ethiopia from Wachemo University. The qualitative data was collected using interviews and reflective journal writing from four instructors taken through convenience sampling among the surveyed instructors on the basis of their willingness to participate. The interview data was transcribed and analyzed applying various stages of coding, employing software called Open Code 4. The journal entry data was analyzed using content analysis method. The quantitative data was analyzed using descriptive statistics applying SPSS version 24. The results revealed that the instructors engaged in the cognitive, practical, affective and meta-cognitive reflections to a greater extent. The findings of the study further demonstrated that although the instructors are relatively good at practicing the four domains of reflection, they rarely engage in critical reflective construct.